(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Cervical cancer is the fourth most common cancer in women worldwide and second mostcommon cancer in developing and under developing Nations. the higher incidence of cervical cancer indeveloping countries is mainly because of lack of resources ,lack of effective screening technologies andpoorly organized health care delivery in the rural areaObjective: To determine the prevalence of cervical precancerous lesion among healthy womenMaterials and Methods: The study was conducted for 600 Healthy women who were selected by usingpurposive sampling technique .the prevalence of precancerous cervical lesion was assessed by VisualInspection with acetic acid and the data was analyzed by using inferential and descriptive statistical methodsResult: It was also observed that prevalence of cervical Precancerous lesions in healthy women was 5.0%.It means that 30(5.0%) out of 600 healthy women had risk of cervical precancerous lesions in this presentstudy. Among the study samples who suspected to be positive, off them 10(3.3%) had two or less quadrantinvolved, and 5 (1.7%) had three quadrants involved, About action taken 30(5.0%) were referred forconfirmation, 230(38.3%) followed up after 3 years, 340(56.7%) had referred medical treatment and VIAtest after six monthsThe study result shows that Reveals that prevalence of cervical Precancerous lesionswas highly associated with visual examination findings such as cervicitis, white discharge, and abnormalfindings .Conclusion: The study results conclude that VIA test can be used as a alternative screeningtechnique for early diagnosis of precancerous lesion among women at low resource setting